Penuntutan terhadap Perkara Anak dalam Sistem Peradilan Pidana Anak di Indonesia - Siti Nurbadaliah; Akhmad Munawar; Indah Dewi Megasari (CV Rewang Rencang, 2023)
Prosecution of children's cases in the juvenile criminal justice system in Indonesia focuses on the principles of restorative justice, which aims at the rehabilitation and social reintegration of children. Even though Law no. 11 of 2012 concerning the Juvenile Criminal Justice System (JCJS) regulates the protection of children's rights, prosecution practices often face obstacles, such as a lack of understanding by law enforcement officials regarding restorative approaches and limited rehabilitation facilities. This research aims to analyze the prosecution mechanism, the role of prosecutors, and the challenges that exist in the juvenile criminal justice system. The research results show the need to strengthen the capacity of law enforcement officers, improve rehabilitation facilities, and community understanding to realize the goals of an effective and fair juvenile criminal justice system.